Exotic and native parrots (Psittaciformes) in Brazilian households: a national survey from iNaturalist - Mendes Spalding, Rafaela; Moraes dos Santos, Matheus; Enrico Ammirati Rodrigues Tosto (Acta Biológica Catarinense, 2026)
Brazil harbors the world’s richest Psittaciformes diversity. This phenomenon is reflected in the widespread culture of keeping birds as companion animals in the country. Comprehensive national data on which parrot species are kept as pets remain scarce, hindering conservation efforts and public policies. This study leverages citizen science data from iNaturalist to conduct a nationwide analysis of parrots kept in Brazilian households. We identified 998 eligible observations, comprising 60 species (37 native, 23 exotic). Results reveal a heterogeneous national pattern, heavily influenced by regional disparities. While exotic species overwhelmingly dominated the records from the Southeast and South, the Northern and Northeastern regions showed a contrasting pattern, with a greater prevalence of native species. The findings demonstrate the utility of citizen science for mapping human-animal interactions at a national scale, providing critical insights into regional trends of native and exotic species prevalence. This data is vital for informing targeted public policies on wildlife trade, conservation, and animal welfare.